Maintenance programmes for flat roofs in existing buildings. Issue 3 (19th June 2017) - Morgado, João; Flores-Colen, Inês; de Brito, Jorge; Silva, Ana
Abstract : Purpose: The purpose of this paper is to propose a maintenance programme for flat roofs in existing buildings, based on the inspection of 26 buildings in-service conditions, located in the Lisbon region, in Portugal. A proactive maintenance of flat roofs in existing buildings allows reducing their pathology, thus improving their performance and service life. Design/methodology/approach: The maintenance plan was established based on the degradation state of the maintenance source elements (MSEs) analysed, the aggressiveness of the surrounding environment and the age of the roofs and maintenance actions carried out during the roofing systems' life cycle. Findings: The maintenance plan proposed in this study includes the prioritization of the interventions, the definition of the required maintenance operations and the definition of the frequency of the intervention, considering the service lives of the MSEs. Research limitations/implications: The study addresses only roofs located in the Lisbon area. Even though a relatively large sample of 26 roofs was used, the findings and conclusions can clearly be extrapolated for a much wider scope. Practical implications: The maintenance plan proposed in this study considers a planning of proactive maintenance operations to continuously and effectively monitor all the relevant MSE. Originality/value: This plan allows minimizing the incidence and spread of defects, thus enabling the optimization of resources, reducing the costs of the entire maintenance system and improving the quality of the built environment.